Does organizational culture matter in the relationship between trust and SMEs performance - Gorondutse, Abdullahi Hassan; Abdullah, Haim Hilman (Emerald Group Publishing Limited, 2018)
Purpose – Although literature indicated that business social responsibility (BSR) is now a common practice and accepted norm among business enterprises globally, the concept is not well understood and its influence on business performance is contradictory.Therefore, based on the stakeholder theory, the purpose of this paper is to examine the association among trust of BSR and the performance of small-scale industries in Nigeria with organizational culture as a moderating factor. Design/methodology/approach – The hypotheses of the study were tested using personally administered survey questionnaires; the study obtained 486 valid questionnaires, which were evaluated using SmartPLS Algorithm and bootstrapping functions. Findings – The research findings were established using SmartPLS Algorithm and bootstrapping functions. According to the results, the research constructs have a satisfactory convergent and discriminant validity. Equally, the overall model has a very high predictive relevance. In addition, the results showed that all the predicting variables explained 40 percent variance in the criterion variable. Thus, the study established strong positive influence of trust of BSR on the small-scale industrial performance. Correspondingly, the study established a strong positive impact of organizational culture on the performance of the small-scale industries. However, the study could not establish the moderating influence of organizational culture on the constructs. Research limitations/implications – The study used perceptions of owner/managers and only small-scale industries. Practical implications – The research findings may be found beneficial to policy makers and academics, particularly in understanding trust of social responsibility, its influence on performance of small-scale industries and fit between organizational culture and strategic direction of a business enterprise. Originality/value – The study offers some meaningful contribution to knowledge on BSR by exploring the mechanisms connecting trust of BSR with performance. Also, research expert in the field of BSR usually explores the advantage of these findings by utilizing the action of BSR on internal and external stakeholders.